2012
DOI: 10.1007/s10511-012-9221-1
|View full text |Cite
|
Sign up to set email alerts
|

North-south asymmetry in solar, interplanetary, and geomagnetic indices

Abstract: Data of hourly interplanetary plasma (field magnitude, solar wind speed, and ion density), solar (sunspot number, solar radio flux), and geomagnetic indices (Kp, Ap) over the period 1970-2010, have been used to examine the asymmetry between the solar field north and south of the heliospheric current sheet (HCS). A persistent yearly north-south asymmetry of the field magnitude is clear over the considered period, and there is no magnetic solar cycle dependence. There is a weak N-S asymmetry in the averaged sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Svirzhevsky et al [49] examined N-S solar poles asymmetry relative to the solar wind speed, plasma density, and some other solar parameters. Asymmetry between the north and south solar fields was observed in the plasma density, solar radio flux, and geomagnetic indices [66]. Consequently, N-S solar asymmetry ( Figure 3a) is an additional chirality trigger alongside with chirality of the right-handed helix orbital trajectory of Earth revolving around Sun (Figure 3c).…”
Section: Gravitational Field Impact On Chemical Reactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Svirzhevsky et al [49] examined N-S solar poles asymmetry relative to the solar wind speed, plasma density, and some other solar parameters. Asymmetry between the north and south solar fields was observed in the plasma density, solar radio flux, and geomagnetic indices [66]. Consequently, N-S solar asymmetry ( Figure 3a) is an additional chirality trigger alongside with chirality of the right-handed helix orbital trajectory of Earth revolving around Sun (Figure 3c).…”
Section: Gravitational Field Impact On Chemical Reactionsmentioning
confidence: 95%
“…It is interesting to note that the "stirring time to achieve 100% ee depends on the number of glass beads and the stirring rate" [72]. In attempt to explain NaClO 3 crystallization data, Kondepudi et al [66][67][68][69][70]73,74] and other researchers [75][76][77][78] attached importance to the experimental fact of stirring. To explain enantioselectivity of NaClO 3 land d-crystals stirring with and without glass beads (Figure 6a,c) many researchers [71,[79][80][81][82][83][84][85][86][87] argued that attrition/grinding was the key factor.…”
Section: Stirring (Helical Flux) Of the Reaction Mass As A Chirality mentioning
confidence: 99%
“…Other study [11] showed the SWS, IMF, and the geomagnetic index Ap exhibited clear heliospheric N-S asymmetries. The N-S asymmetry for different solar activity features (solar proton events, solar active prominences, Hα flare index, soft X-ray flares, monthly mean sunspot area and sunspot number) have been examined by [12], showing the solar cycle 23 rd was magnetically weak compared to solar cycle 22 nd .…”
Section: Introductionmentioning
confidence: 99%
“…The work [16] showed that the N-S asymmetries are found in the declining and increasing phases, as well as times of maxima for all solar cycles that he studied. Sanalkumaran and Prabhakaran [17], examined the N-S asymmetry for IMF, Ap, and V during the four cycles (20)(21)(22)(23) and he found the phase of the asymmetry of IMF reverse every cycle, and the asymmetry of the Ap index appears similar to that of solar wind velocity and may be due to the existence of relic magnetic field in the solar convection zone. The Sun's magnetic activity is generally believed to be supplied by a hydromagnetic dynamo operating either in or at the base of the solar convective zone.…”
Section: Introductionmentioning
confidence: 99%
“…Beside that El-Borie et al [21], examined the N-S asymmetry for the plasma parameters and the solar indices an he said that the N-S asymmetry for the solar plasma was more dense north of the current sheet than south of it during the second negative solar polarity epoch (qA < 0). In the present work, we examine the N-S asymmetries in the solar and interplanetary parameters (Field magnitude (B), Solar wind speed V, Proton density n, and the Proton temperature T) during the period from 1975 to 2013.…”
Section: Introductionmentioning
confidence: 99%